2016
DOI: 10.2507/26th.daaam.proceedings.042
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Modelling and Simulation Software System for Adaptive Engineering of Hydraulic Gear Pumps

Abstract: The paper presents an analysis and validation method for a CAD model of a spur gear pumps series using FEM simulations. The analyzed pump is a new improved variant chosen among several constructive solutions created by parametric aided design in a range of gear pumps. Using mathematical computations and a calculus methodology there were identified the pressure values and forces generated in the pump assembly. The proposed study is especially applied to the gearing area and to the outlet chamber, where values a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Knowing the simulation practices with FEM and analyzing all these results presented in tables, it can be concluded that the parameterized variants of the pump model meet the conditions for manufacturing [24]. Knowing the simulation practices with FEM and analyzing all these results presented in tables, it can be concluded that the parameterized variants of the pump model meet the conditions for manufacturing [24].…”
Section: Simulation With Finite Elements Of the Spur Gear Loadsmentioning
confidence: 94%
“…Knowing the simulation practices with FEM and analyzing all these results presented in tables, it can be concluded that the parameterized variants of the pump model meet the conditions for manufacturing [24]. Knowing the simulation practices with FEM and analyzing all these results presented in tables, it can be concluded that the parameterized variants of the pump model meet the conditions for manufacturing [24].…”
Section: Simulation With Finite Elements Of the Spur Gear Loadsmentioning
confidence: 94%
“…Of course, despite these constraints, the project's cost should be optimal and the resulted prototype reliable and affordable for mass industrial production. Conception and development of a new magnetic drive pump rises some risks: the magnetic field creation system required to drive the pump may have a high energy consumption; high costs for experiments and validation of the pump variant; dissipation of the magnetic flux inside the pump without a proper driving effect [1]; certain functional requirements [2] may not be fulfilled by the functional prototype, leading to a decrease of the prescribed pressure and the appearance of certain worn areas; the choice of the metallic and polymeric composite materials may require further laborious researches; difficulties in balancing the resulting forces from pump operation [6], etc.…”
Section: Scientific and Industrial Relevancementioning
confidence: 99%